3 - Financing a Public University: Strategic Directions for Makerere University in Uganda - Elisam Magara, (Journal of Higher Education in Africa, 2009)
Public universities all over the world are continually facing challenges arising from increasing expectations from government and the public for universities to serve the broader needs of society. This has impacted the universities’ ability to offer their core functions of teaching and learning, research and outreach. This paper reviews the current resource allocation models, reforms and developments of higher education in Uganda. Despite the available options of funding strategies (donor contributions, government support and the Appropriation in Aid [AIA]), Makerere University still faces the dilemma of unfinished business. It was thus established that the block allocation model currently used by Makerere University, which is based on fixed percentages to units, has led to a lack of co-ordination of services in the university. This has led to the difficulty in supporting university-wide services. This paper attempts, therefore, to provide strategic directions for Makerere University in ensuring effective resource allocation and prioritisation of the University budget in accordance with its core functions. The paper does so by suggesting restructuring from the current percentage- based budgeting to activity-based budgeting and expenditure allocation where the budgets clearly outline the activities expected in the various units for the financial year.